Dual backstepping variable structure switching control of bounded uncertain nonlinear system. Issue 11 (18th August 2022) - Yin, Qitian; Bian, Yixin; Du, Jun; Zhao, Wei; Yang, Shengbin
Abstract : This paper proposes a dual backstepping variable structure switching control strategy to realise the stable reference signal tracking of bounded uncertain nonlinear system. Compared with the conventional backstepping control scheme, the proposed approach contains double distinct backstepping recursive sequences instead of the single sequence. According to the saturation switching condition, the first backstepping sub-controller is applicable to the saturation switching phase to ensure stability in a large region. The second backstepping sub-controller is applicable to the linear transient phase to shrink the convergence domain further for improving the control performance. The proposed control mechanism consists of double distinct backstepping sub-controllers which are regulated and tuned based on variable structure switching logic. The most significant advantage is that the switching controllers expand the traditional single backstepping variable structure control to double backstepping. This method not only guarantees the tracking error global uniform convergence but also improves the tracking control performance. In addition, this method absorbs both the advantages of backstepping and variable structure to protect the beneficial nonlinear properties in states and suppress the chatting. To evaluate the control performance and tracking effectiveness of the proposed control mechanism, a numerical comparing example is presented and discussed.